2021
DOI: 10.1002/saj2.20134
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of subsoil pore characteristics and hydraulic conductivity as affected by compaction and cover crop treatments

Abstract: The natural and cover crop (CC)‐induced anisotropy of subsoil pore characteristics is important in assessments of soil compaction but, until recently, has received limited attention. This study aims to quantify the anisotropy of soil pore characteristics and hydraulic conductivity in subsoils subjected to compaction and CC treatments in a split‐plot field experiment on temperate sandy loam soils. The main factor was ±compaction and the split‐plot factor was ±CC with fodder radish (Raphanus sativus L.). The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 60 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…The degree of anisotropy (Figure 5c) reflects the arrangement of soil pores in different directions [58,59]. Our study observed the highest 𝐷𝐴 values for NT, although minor differences (p>0.05) were observed between treatments.…”
Section: Resultsmentioning
confidence: 50%
“…The degree of anisotropy (Figure 5c) reflects the arrangement of soil pores in different directions [58,59]. Our study observed the highest 𝐷𝐴 values for NT, although minor differences (p>0.05) were observed between treatments.…”
Section: Resultsmentioning
confidence: 50%